Construction of a Protective Vaccine Against Lipopolysaccharide-Heterologous Pseudomonas aeruginosa Strains Based on Expression Profiling of Outer Membrane Proteins During Infection - Liu, Chang; Pan, Xiaolei; Xia, Bin; Chen, Fei; Jin, Yongxin; Bai, Fang; Priebe, Gregory; Cheng, Zhihui; Jin, Shouguang; Wu, Weihui (Frontiers in Immunology, 2018)
Pseudomonas aeruginosa is a ubiquitous opportunistic pathogen, which causes infectious disease in patients with cystic fibrosis and compromised immunity. P. aeruginosa is difficult to eradicate because of its intrinsic resistance to most traditional antibiotics as well as acquired resistance mechanisms after decades of antibiotic usage. A full understanding of the P. aeruginosa pathogenesis mechanisms is necessary for the development of novel prevention and treatment strategies. To identify novel vaccine candidates, here we comprehensively examined the expression levels of all the known outer membrane proteins in two P. aeruginosa strains in a murine acute pneumonia model. OprH was one of the most highly expressed proteins during infection. In addition, OprH is known to be highly immunogenic and accessible by host proteins. Thus, it was chosen as a vaccine candidate. To further identify vaccine candidates, 34 genes highly expressed during infection were evaluated for their contributions in virulence by testing individual transposon insertion mutants. Among them, fpvA, hasR and foxA were found essential for bacterial virulence and therefore included in vaccine construction. Immunization with a mixture of FpvA, HasR and FoxA rendered no protection, however, while immunization by OprH refolded in liposomes elicited specific opsonic antibodies and conferred protection against two lipopolysaccharide-heterologous P. aeruginosa strains (PA14 and PA103). Overall, by studying the expression profile of the P. aeruginosa outer membrane proteins during infection, we identified OprH as a potential vaccine candidate for the prevention of lung infection by P. aeruginosa.